Deductive and Inductive Methods in Teaching Tenses - Saadiyah Arifin (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2016)
Teaching English grammar seems easy but difficult to conduct. Some methods have been introduced to answer this problem. Two methods that have been known so far are deductive and inductive methods. Studies have been conducted concerning these methods, with some supporting deductive while the others being in favor of inductive method. This study attempts to investigate which method works better in facilitating students’ writing skill. The findings of this experimental study (n=40) taking place in one of English course in Jakarta show that deductive method is more effective in promoting students’ writing skill.